Strategi Komunikasi Pemasaran Perusahaan Dalam Upaya Meningkatkan Penjualan Minuman Waralaba di Era Disrupsi - Fatharani, Juniar; Paryati, Paryati; Ma’arif, Abdul Aziz (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2022)
The aim of this research is to analyze and identify marketing communication strategies that can be used by franchised beverage companies in facing changes and challenges in the era of disruption. The method of data collection will be carried out through in-depth interviews with related parties in the company, direct observation of marketing communication practices carried out, as well as analysis of marketing documents and materials used by the company. The results of this study are expected to provide insight into effective marketing communication strategies in increasing franchised beverage sales in the disruption era. Factors that influence the success of a marketing communication strategy also include product, price, place and promotion, including the use of social media, digital technology, message personalization, and utilization of consumer data. This research will contribute to the understanding of how companies can face challenges in the era of disruption and optimize their marketing communications to achieve business success.